Self-reported impairments among people with late effects of polio: a mixed-methods study - Catharina Sjödahl Hammarlund; Jan Lexell; Christina Brogårdh (Medical Journals Sweden, 2020)
Objective: To determine how much people with late effects of polio are bothered by various impairments and their influence on everyday life. Design: A mixed-methods design. Subjects/patients: Seven women and 7 men (mean age 70 years) with late effects of polio. Methods: Self-reported Impairments in Persons with late effects of Polio (SIPP) scale and face-to-face interviews. In SIPP, the participants rated, from 1 (not at all) to 4 (extremely), how much they had been bothered by late effects of polio-related impairments. Qualitative data were analysed using systematic text condensation. Each quotation was deductively analysed based on its conceptual representation regarding perceived influence on everyday life. Results: Participants were most bothered by muscle and/or joint pain during physical activity, muscle weakness and general fatigue, which corresponded with the number of interview quotations. The impairments negatively influenced daily life, such as household chores, walking, riding a bicycle and social participation. Increased impairments and reduced functioning on the less-affected side also caused worry and distress. Conclusion: Common late effects of polio-related impairments greatly affected participants' activity and participation. By using both the SIPP scale and face-to-face interviews, an increased understanding of how late effects of polio-related impairments influence everyday life was achieved.